ADVANCED TRANSIENT THERMAL AND STRUCTURAL ANALYSIS OF DISC BRAKE BY USING ANSYS IN TWO WHEELER - Mr.Ingale S.P.; Prof.Patel A.Z.; Prof.Ghalake A.B. (International Journal of Innovations in Engineering Research and Technology, 2021)
n these paper structural fields of the solid disc brake during short and emergency braking with four different materials is studied. The distribution of the temperature depends on the various factors such as friction, surface roughness and speed. The effect of the angular velocity and the contact pressure induces the temperature rise of disc brake. The finite element simulation for three-dimensional model was preferred due to the heat flux ratio constantly distributed in circumferential direction. Here value of temperature, friction contact power, nodal displacement and deformation for different pressure condition using analysis software with four materials namely cast iron, cast steel, aluminium and carbon fibre reinforced plastic are taken. Presently the Disc brakes are made up of cast iron and cast steel. With the value of simulation result best suitable material for the brake drum with higher life span is determined.